Toward compatibility with national dairy production and climate goals through locally appropriate mitigation interventions in Kenya - Graham, Michael W.; Özkan, Şeyda; Arndt, Claudia; González-Quintero, Ricardo; Korir, Daniel; Merbold, Lutz; Mottet, Anne; Ndung'u, Phyllis W.; Notenbaert, An; Leitner, Sonja M. (Elsevier, 2024)
Livestock are an important component of livelihoods in smallholder dairy systems in Africa, but are characterized by low animal productivity and large environmental impacts per unit of animal product (e.g. greenhouse gas emissions (GHG) intensities). Governments in African countries have set ambitious targets for dairy systems, but development of climate-smart strategies has been hindered by a scarcity of baseline data and local intervention trials. We use a rich dataset from smallholder mixed dairy systems in Kenya to determine whether national climate and development goals for 2030 can be met using locally appropriate interventions. Interventions considered included improved herd management and feed interventions. We conducted a yield gap analysis to determine the scope of the existing milk yield gaps, then evaluated the extent to which yield gaps could be closed using interventions in a second step. We outscaled our results to the national level to determine the potential impact of adopting our interventions on national dairy production and GHG emission goals using the FAO Global Livestock Environmental Assessment Model – interactive (GLEAM-i) tool. Our analysis showed that substantial yield gaps exist in Kenyan dairy systems (39 to 49% of attainable yields). These gaps could be closed by intervention packages but not by individual interventions alone. Our outscaled scenarios showed interventions can reduce milk GHG emission intensities (−6.5 to −27.4%), while absolute emissions would increase in most scenarios (−3.9 to +25.9%). To meet national milk production goals, we estimated that a large increase in animal numbers is needed by 2030 compared to 2010 (from ∼2.7 M to 4.5–7.1 M heads of cattle). However, most scenarios fell short of the emissions target (−4% to +48%) by 2030. It may be possible to narrowly meet Kenyan national milk production and GHG emission goals by 2030.